Global modeling of tropospheric iodine aerosol. Issue 18 (30th September 2016) - Sherwen, Tomás M.; Evans, Mat J.; Spracklen, Dominick V.; Carpenter, Lucy J.; Chance, Rosie; Baker, Alex R.; Schmidt, Johan A.; Breider, Thomas J.
Abstract: Natural aerosols play a central role in the Earth system. The conversion of dimethyl sulfide to sulfuric acid is the dominant source of oceanic secondary aerosol. Ocean emitted iodine can also produce aerosol. Using a GEOS‐Chem model, we present a simulation of iodine aerosol. The simulation compares well with the limited observational data set. Iodine aerosol concentrations are highest in the tropical marine boundary layer (MBL) averaging 5.2 ng (I) m −3 with monthly maximum concentrations of 90 ng (I) m −3 . These masses are small compared to sulfate (0.75% of MBL burden, up to 11% regionally) but are more significant compared to dimethyl sulfide sourced sulfate (3% of the MBL burden, up to 101% regionally). In the preindustrial, iodine aerosol makes up 0.88% of the MBL burden sulfate mass and regionally up to 21%. Iodine aerosol may be an important regional mechanism for ocean‐atmosphere interaction. Key Points: Model of iodine aerosol shows skill in reproducing observations Highest iodine mass is in the tropical marine boundary layer, up to 101% of DMS sulfate aerosol Regionally iodine aerosol is up to 11% of total sulfate and higher (21%) in the preindustrial